2018
DOI: 10.1037/pas0000519
|View full text |Cite
|
Sign up to set email alerts
|

Initial validation of brief measures of suicide risk factors: Common data elements used by the Military Suicide Research Consortium.

Abstract: The Military Suicide Research Consortium (MSRC) developed a 57-item questionnaire assessing suicide risk factors, referred to as the Common Data Elements (CDEs), in order to facilitate data sharing and improve collaboration across independent studies. All studies funded by MSRC are required to include the CDEs in their assessment protocol. The CDEs include shortened measures of the following: current and past suicide risk, lethality and intent of past suicide attempts, hopelessness, thwarted belongingness, anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 52 publications
4
76
0
Order By: Relevance
“…Most items were taken from existing measures that assess constructs like PTSD, hopelessness, alcohol use, insomnia, and suicidality, though some were created by MSRC personnel. Overall, the CDE items demonstrate convergence with the scales they were derived from (Ringer et al, ). Our interoceptive deficits latent variable was created from these items.…”
Section: Studymentioning
confidence: 56%
“…Most items were taken from existing measures that assess constructs like PTSD, hopelessness, alcohol use, insomnia, and suicidality, though some were created by MSRC personnel. Overall, the CDE items demonstrate convergence with the scales they were derived from (Ringer et al, ). Our interoceptive deficits latent variable was created from these items.…”
Section: Studymentioning
confidence: 56%
“…Higher scores on each of these measures indicate greater severity of each respective construct assessed. Research supports the reliability and validity of the MSRC CDEs’ abbreviated measures of the aforementioned constructs among military service members and veterans (Ringer et al, ). In this sample, internal consistency across the MSRC CDEs’ abbreviated measures ranged from acceptable to strong (αs = 0.75–0.92; see Table ).…”
Section: Methodsmentioning
confidence: 81%
“…Instead, as noted, the CDEs reflect a collection of items assessing suicide-related constructs that are standardized across MSRC-funded studies as well as other studies examining suicide-related topics among military populations. Ringer et al (2018) found robust psychometric support for item subsets (e.g., they were highly correlated with their full parent measures, suggesting they assess the same construct). These item subsets also demonstrated acceptable-to-excellent internal consistency (Ringer et al, 2018).…”
Section: Methodsmentioning
confidence: 90%